Analisis Pengaruh Jumlah Tugas Terhadap Tingkat Burnout Mahasiswa PPNS - Nina Aulya Wibowo; Mazida Rahmawati; Irina Kartika Utami; Denny Oktavina Radianto (Student Scientific Creativity Journal, 2023)
Higher education aims to hone the abilities and competencies needed in the future. In the lecture process, students required to complete assignments. The large number of assignments makes students often cause burnout. The technique applied is quantitative techniques using cross-sectional design. Sampling using questionnaires with a variable number of tasks and a variable burnout rate the value of the regression coefficient for the number of tasks shows a value of 0.853, indicating that the variable number of tasks has a positive influence on the burnout rate. The variable significance value of the number of tasks is 0.28, where the value is 0.05. The results of the hypothesis test prove that the number of tasks had a substantial and positive caused on the burnout rate.